Controlling Dissolution and Transformation of Zeolitic Imidazolate Frameworks by using Electron‐Beam‐Induced Amorphization. Issue 41 (19th September 2018) - Conrad, Sabrina; Kumar, Prashant; Xue, Feng; Ren, Limin; Henning, Sheryl; Xiao, Chunhong; Mkhoyan, K. Andre; Tsapatsis, Michael
Abstract: Amorphous zeolitic imidazolate frameworks (ZIFs) offer promising applications as novel functional materials. Herein, amorphization of ZIF‐L through scanning‐electron‐beam exposure is demonstrated, based on amorphization of individual ZIF‐L crystals. The amorphized ZIF product has drastically increased stability against dissolution in water. An electron dose that allows for complete preservation of amorphous particles after immersion in water is established, resulting in new shapes of amorphous ZIF‐L with spatial control at the sub‐micrometer length scale. Changed water stability as a consequence of scanning‐electron‐beam exposure is demonstrated for three additional metal–organic frameworks (ZIF‐8, Zn(BeIm)OAc, MIL‐101), highlighting the potential use of an electron beam for top‐down MOF patterning. Lastly, recrystallization of ZIF‐L in the presence of linker is studied and shows distinct differences for crystalline and amorphized material. Abstract : Scanning ‐electron‐beam‐induced amorphization of zeolitic imidazolate framework L with control at the sub‐micrometer scale occurs without loss of macroscopic integrity and entails a significant increase in water stability, which gives access to novel morphologies of the amorphized product.